Recalcitrant Female Pattern Hair Loss Like Alopecia Unveils Unexpected Rare Entity - Nouh AH; Elgendy FM; Gobran FA; Zhuravlova MS (Clinical, Cosmetic and Investigational Dermatology)
Ahmed H Nouh,1 Fatma M Elgendy,2 Fatma A Gobran,3 Maryna S Zhuravlova4 1Al-Azhar University, Faculty of Medicine, Department of Dermatology, Venereology and Andrology, Cairo, Egypt; 2Ain Shams university, Faculty of medicine, Department of Pathology, Cairo, Egypt; 3Medical Laboratory at Sharkia Health Directorate, Ministry of Health, Belbeys, Egypt; 4Lugansk state medical University, Department of Pathology, Rivne, UkraineCorrespondence: Maryna S Zhuravlova, Email marynazhuravlovamd@gmail.comIntroduction: Marie-Unna hereditary hypotrichosis (MUHH) is an autosomal dominant disorder characterized by a specific pattern of hair loss. Initially described in 1925 by Marie-Unna in a German family spanning over seven generations, MUHH represents a previously unidentified form of congenital hypotrichosis. It typically presents as sparse hair at birth with a coarse texture, followed by regrowth during childhood then, finally, gradual hair loss at puberty, resembling pattern of androgenetic alopecia.Case Presentation: The study describes two cases from different unrelated families presenting with recalcitrant alopecia resembling female pattern hair loss, with dermoscopic findings consistent with pili torti and yellow dots. Genetic testing confirmed a heterozygous pathogenic variant in the HRURF gene, associated with autosomal dominant Marie Unna Hereditary Hypotrichosis. Up to our knowledge it is first case series reported from Egypt.Conclusion: While recent literature on MUHH has primarily focused on identifying genetic abnormalities, there are other important questions that warrant consideration. These include histopathological studies, dermoscopic descriptions, and correlating types of genetic mutations with clinical presentations. These data might offer a deeper understanding of MUHH pathophysiology ending in efficacious treatment options.Plain language summary: Marie-Unna hereditary hypotrichosis (MUHH) is a rare genetic condition that causes a distinct pattern of hair loss. First identified in 1925 in Germany, this condition is passed down through families. In this article, we report two unrelated cases from Egypt, marking the first documented cases of MUHH in the country. Each case involves different genetic mutations, highlighting the variability of the condition.MUHH typically presents as sparse hair at birth, which becomes coarse in childhood and then gradually thins again during puberty. This hair loss can resemble common male-pattern baldness. While MUHH mainly affects hair, it may also be linked to other conditions such as skin tumors (trichoepithelioma), limb abnormalities, eye issues, wide-spaced teeth, and syndromes like Ehlers-Danlos or atopy.Because MUHH is so rare, diagnosing it can be difficult, and many healthcare providers may not immediately recognize it. By describing these cases, we aim to raise awareness and improve understanding of MUHH, encouraging clinicians to consider it as a possible diagnosis in similar presentations.Keywords: hair disorder, rare genetic disorder, alopecia, madarosis, hereditary hypotrichosis